Ten simple rules for good model-sharing practices. - Ismael Kherroubi Garcia; Christopher Erdmann; Sandra Gesing; Michael Barton; Lauren Cadwallader; Geerten Hengeveld; Christine R Kirkpatrick; Kathryn Knight; Carsten Lemmen; Rebecca Ringuette; Qing Zhan; Melissa Harrison; et al. (PLoS Computational Biology)
Computational models are complex scientific constructs that have become essential for us to better understand the world. Many models are valuable for peers within and beyond disciplinary boundaries. However, there are no widely agreed-upon standards for sharing models. This paper suggests 10 simple rules for you to both (i) ensure you share models in a way that is at least "good enough," and (ii) enable others to lead the change towards better model-sharing practices.